Illustrative case series of intra-abdominal abscesses - a radiological viewpoint - S. A. S. R. Siriwardana; P. D. Anjula (Asian Journal of Internal Medicine)
Intra-abdominal abscesses (IAA) may commonly arise following complicated gastrointestinal tract infections and, on occasion, from infections within the urinary system. Many of these IAA arise as a consequence of post-surgical complications. These abscesses have a substantial risk of morbidity and mortality. It is crucial to diagnose and treat them to minimise these adverse outcomes promptly. Radiological modalities play a vital role in diagnosing, localising, and detecting associated complications of IAA, as sometimes other investigations can be less reliable and non-specific. Radiological techniques such as ultrasound scans (USS), contrast-enhanced computed tomography (CECT), and even magnetic resonance imaging (MRI) are immensely helpful in diagnosing these conditions. These imaging tools guide clinicians in determining the most appropriate patient management strategies. In this article, we compile a case series involving tubo-ovarian abscess, appendicular abscess, diverticular abscess and infected walled-off pancreatic necrosis, delineating characteristic radiological features which aid in their diagnosis.